MODERN INTERPRETATION IN STENOGRAPHY OF THE BALLET “LAZGI - DANCE OF HEART AND LOVE” ON THE STAGE OF THE STATE ACADEMIC BIG THEATER NAMED AFTER ALISHER NAVOI - Imankulova Inobat Maxkambaevna (Scholar Express Journal, 2021)
The author of the article explored the modern interpretation of the ballet “Lazgi – Dance of Heart and Love” on the stage of the State Academic Bolshoi Theater named after Alisher Navoi.
Keywords: Scenography; flow; style; space